Paying adolescents for health screenings works - Martin Halla; Gerald J. Pruckner; Thomas Schober (Johannes Kepler Universität Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2021)
With regard to their future health, adolescents are at a critical stage. Previous evaluations have shown that health screenings, counselling, and other intervention programmes during this phase of life are important, particularly for those with a low socio-economic background. Unfortunately, adolescents tend to have little interest in preventive programmes. We designed a field experiment to evaluate the effectiveness of financial incentives to promote participation in health screenings. Our study comprises more than 10,000 participants, observed via high-quality administrative data from Austria. The treatment group received a e40 shopping voucher if they participated in an age-specific health screening. On average, the financial incentive increased the likelihood of participation by 280 %. Treatment effects are comparably larger for children in families with a higher socio-economic status, and of parents with a revealed preference for secondary health prevention.
Keywords: I12; J13; I18; I14; H51; H75; 330; health screenings; financial incentives; adolescence; early intervention; secondary prevention